Age-related experiences of diverse older women living with HIV: A scoping review protocol informed by intersectionality. - Kristina Kokorelias; Paige Brown; Sharon Walmsley; Alice Zhabokritsky; Esther Su; Luxey Sirisegaram (PLoS ONE)
Introduction Older women living with HIV often go unnoticed due to societal biases and stigmas. Despite a rise in cases among older women, there is limited research on the psychosocial factors impacting their experiences. Aging complexities compounded by HIV and menopause affect these women's health, while factors like mental health impact, changing support networks, and ageism with HIV stigma influence their well-being. Existing studies mostly compare older HIV-positive individuals without considering gender and intersectional identities, limiting understanding of their unique experiences. The scarcity of research addressing age-related differences from diverse perspectives delays the development of tailored treatments and interventions. Objectives The study aims to comprehensively explore the age-related experiences of older women with HIV through three sub-questions that address (1) Key experiences, medical and social challenges, and strengths; (2) Impact of intersectional identities on their experiences; and (3) Gaps and limitations in current research. Methods Utilizing a scoping review approach, the study seeks to map existing literature, employing a theoretical framework rooted in Sex- and Gender-Based Analysis Plus (SGBA+). Articles focusing on the age-related experiences of older women living with HIV aged 50 and above will be included. The study selection process will involve two independent reviewers screening articles based on pre-established inclusion criteria. Data extraction and synthesis will follow, analyzing the influence of sex, gender, and other identities on experiences. Discussion The study's comprehensive approach aims to bridge gaps in understanding older women's HIV experiences, emphasizing intersectionality. While limited to English-language peer-reviewed articles, this review seeks to offer valuable insights for healthcare, policy, and research, potentially fostering positive change in the lives of diverse older women living with HIV.